A review on transdermal spray: formulation aspect - Mandal, Uttam Kumar; Chatterjee, Bappaditya; Pauzi, Fatin Husna (Mathews Open Access Journals, 2016)
Transdermal spray offers numerous advantages over the other conventional transdermal drug delivery forms such as gel, ointment and patches, in terms of its cosmeceutical appearance, ready availability for application, flexibility in dosage design, less occurrence of skin irritation and faster drying rate from the application site due to the use of volatile solvent. However, compared to other transdermal drug delivery dosage forms, transdermal spray has the least and limited number of products approved for marketing. Among the drugs are, Evamist®, an estradiol formulation approved in 2007 by the FDA followed by Axiron® a non-spray solution to treat low testosterone in men and Recuvyra®, a pain reliever solution indicated for dogs. This review article focuses current status on the formulation and evaluation of transdermal spray in the background of the role and effects of its composition specially the selection of drugs, volatile solvents, penetration enhancers and film forming polymer, etc. The limitation of transdermal spray highlighted in this review is the concern of its use, especially, the third party exposure particularly for endocrinology indication. Moreover, transdermal spray is also restricted in drugs with large doses due to the limited diffusivity into the skin. The difficulty of exploiting hydrophilic drugs like peptides, macromolecules and new genetic treatments using DNA or small-interfering RNA (siRNA) into transdermal spray formulations is also a limitation that needs to be explored in depth.